Associations of parent dietary role modeling with children's diet quality in a rural setting: Baseline data from the NU-HOME study. (1st July 2022) - Linde, Jennifer A.; Horning Dehmer, Melissa L.; Lee, Jiwoo; Friend, Sarah; Flattum, Colleen; Arcan, Chrisa; Fulkerson, Jayne A.
Abstract: These analyses examined associations of parent dietary role modeling with diet quality among school-age children in a rural community. Past research has found protective associations between parent role modeling and children's dietary intake; however, there is a gap in understanding these associations for families in rural communities. Baseline data (2017 -2018) were drawn from the New Ulm at Home (NU-HOME) randomized controlled trial, conducted in the United States. The trial recruited 114 children (7–10 years old) and parents. Parents self-reported dietary intake [fruit and vegetable (FV), sugar-sweetened beverage (SSB), fast food (FF)] and frequency of sitting and eating with their child. Children reported parent role modeling of healthful eating (FV and salad at the evening meal; FV as snacks). Two 24-h dietary recalls assessed child diet quality indicators [Healthy Eating Index-2015 (HEI-2015) total scores, FV intake, SSB intake]. General linear models (GLM) and logistic regression analyzed associations of child diet quality (HEI score, FV intake, SSB intake) with parent dietary intake, parent sitting and eating the evening meal with their child, and child perceptions of parent role modeling healthful eating, adjusted for highest level of education in the home. Higher child HEI-2015 scores were positively associated with more frequent parent role modeling of fruit intake at meals, and inversely associated with more frequent parent role modeling of fruit as a snack; no significant associations of child FV intake with parent role modeling were observed. Higher child SSB intake was positively associated with parent FF intake. In this rural community, parents play significant roles in shaping children's dietary quality and intake, though more work needs to be done to address optimal intervention strategies to promote parent role modeling of healthful eating.